Analyzing the Correlation Between Students’ Motivation and Error Pronunciation of Voiceless Θ Words: A Qualitative Study - Adara, Reza Anggriyashati; Zulaeha, Elli Rahmawati; Arianto, Anggiarini; Kamilah, Wilda; Najmudin, Onin (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Pronunciation can be considered as one of the most difficult aspects to acquire in second language acquisition. Analyzing pronunciation errors may provide teachers and researchers on the best approaches to teach pronunciation. In addition, it has been suggested that students who are interested in correcting their pronunciation errors can be more motivated to acquire the target language. Thus, the present study aims to analyze the relationship between pronunciation errors of voiceless θ words and students’ motivation. The present study applied a descriptive qualitative approach by interviewing 15 students from a senior high school in Bekasi, Indonesia. The results of present study suggest that the majority of the respondents found it difficult to pronounce voiceless θ words. However, their difficulties to pronounce voiceless θ words might not correlate with their motivation to learn English as the majority of the respondents are motivated to learn English despite finding difficulties to pronounce voiceless θ words. Furthermore, the majority of the participants are motivated to improve their pronunciation due to extrinsic factors. Implications and further studies are also discussed in the present study.Keywords: Motivation, Pronunciation Errors, Qualitative Study, Voiceless Θ Words